Mitochondrial-regulated Tregs: potential therapeutic targets for autoimmune diseases of the central nervous system - Han, Aoya; Peng, Tingting; Xie, Yinyin; Zhang, Wanwan; Sun, Wenlin; Xie, Yi; Ma, Yunqing; Wang, Cui; Xie, Nanchang (Frontiers in Immunology, 2023)
Regulatory T cells (Tregs) can eliminate autoreactive lymphocytes, induce self-tolerance, and suppress the inflammatory response. Mitochondria, as the energy factories of cells, are essential for regulating the survival, differentiation, and function of Tregs. Studies have shown that patients with autoimmune diseases of the central nervous system, such as multiple sclerosis, neuromyelitis optica spectrum disorder, and autoimmune encephalitis, have aberrant Tregs and mitochondrial damage.However, the role of mitochondrial-regulated Tregs in autoimmune diseases of the central nervous system remains inconclusive. Therefore, this study reviews the mitochondrial regulation of Tregs in autoimmune diseases of the central nervous system and investigates the possible mitochondrial therapeutic targets.